Comportamento de propriedades físicas, químicas e reológicas do suco de acerola armazenado a baixa temperatura - Gomes, José E. [UNESP]; Perecin, Dilermando [UNESP]; Martins, Antônio B. G. [UNESP]; Fontes, Sérgio R. [UNESP] (Departamento de Engenharia Agrícola - UFCG, 2001)
With the objective to study physical, chemical and rheological behavior of West Indian cherry juice of five genotypes (CL2, CL5, CL11, R1 and R2) an experiment was conducted with the juice extracted from 2 kg of mature fruits after washing, dried and squashed in a manual processor. The juice was sieved in a 1.6 mm sieve; 20 mL samples were packed in plastic tubes (5 x 3 cm) and stored in a freezer at -10 °C for a 10 month period. The evaluations of total soluble solids were refractometric, the pH was determined by potentiometer, vitamin C was measured by iodine reduction technique and apparent viscosity determined in concentric cylinders viscosimeter. The determinations were done initially and at intervals of two months (0, 2nd, 4th, 6th, 8th and 10th). Viscosity and vitamin C were the characteristics which varied highly. The genotype CL-2 surpassed other genotypes in total soluble solids and the genotypes R1 and R2 showed superiority in vitamin C content. The analyzed juices presented a non-newtonian and pseudoplastic rheological behavior.

Estudou-se o comportamento físico, químico e reológico do suco de cinco genótipos de acerola (CL2, CL5, CL11, R1 e R2) depois de lavadas, as frutas (2 kg) foram esmagadas em um processador manual. Do extrato obtido, em peneira de 1,6 mm, para separar o suco dos resíduos e sementes, foi acondicionado 20 mL de suco de cada amostra em tubos plásticos com dimensões 5 x 3 cm, que foram armazenados em freezer a uma temperatura de -10 °C, durante 10 meses. As leituras de sólidos solúveis totais foram refratométricas, o pH foi aferido através de um potenciômetro, o teor de vitamina C pela técnica da redução do iodo e a viscosidade aparente com viscosímetro de cilindros concêntricos. As determinações foram realizadas inicialmente (mês 0) e bimestralmente (2°, 4°, 6°, 8° e 10° mês). Os parâmetros de viscosidade e vitamina C foram os que mais variaram. O genótipo CL-2 se destacou no teor de sólidos solúveis totais e os R1 e R2 em teores de vitamina C. Os sucos analisados mostraram comportamento reológico não-newtoniano e pseudoplástico.
Physical, chemical and rheological behavior of West Indian cherry juice stored at low temperature
Keywords: Malpighia punicifolia; physical-chemical behavior; juice; viscosity; vitamin C; Malpighia punicifolia; vitamina C; suco; viscosidade